Asia Pacific consensus recommendations for colorectal cancer screening. Issue 8 (15th July 2008) - Sung, J J Y; Lau, J Y W; Young, G P; Sano, Y; Chiu, H M; Byeon, J S; Yeoh, K G; Goh, K L; Sollano, J; Rerknimitr, R; Matsuda, T; Wu, K C; et al.
Abstract : Colorectal cancer (CRC) is rapidly increasing in Asia, but screening guidelines are lacking. Through reviewing the literature and regional data, and using the modified Delphi process, the Asia Pacific Working Group on Colorectal Cancer and international experts launch consensus recommendations aiming to improve the awareness of healthcare providers of the changing epidemiology and screening tests available. The incidence, anatomical distribution and mortality of CRC among Asian populations are not different compared with Western countries. There is a trend of proximal migration of colonic polyps. Flat or depressed lesions are not uncommon. Screening for CRC should be started at the age of 50 years. Male gender, smoking, obesity and family history are risk factors for colorectal neoplasia. Faecal occult blood test (FOBT, guaiac-based and immunochemical tests), flexible sigmoidoscopy and colonoscopy are recommended for CRC screening. Double-contrast barium enema and CT colonography are not preferred. In resource-limited countries, FOBT is the first choice for CRC screening. Polyps 5–9 mm in diameter should be removed endoscopically and, following a negative colonoscopy, a repeat examination should be performed in 10 years. Screening for CRC should be a national health priority in most Asian countries. Studies on barriers to CRC screening, education for the public and engagement of primary care physicians should be undertaken. There is no consensus on whether nurses should be trained to perform endoscopic procedures for screening of colorectal neoplasia.